Prevalence and risk of violence against people with and without disabilities: findings from an Australian population‐based study. (29th December 2015) - Krnjacki, Lauren; Emerson, Eric; Llewellyn, Gwynnyth; Kavanagh, Anne M.
Abstract: Objectives : There are no population‐based estimates of the prevalence of interpersonal violence among people with disabilities in Australia. The project aimed to: 1) estimate the prevalence of violence for men and women according to disability status; 2) compare the risk of violence among women and men with disabilities to their same‐sex non‐disabled counterparts and; 3) compare the risk of violence between women and men with disabilities. Methods : We analysed the 2012 Australian Bureau of Statistics Survey on Personal Safety of more than 17, 000 adults and estimated the population‐weighted prevalence of violence (physical, sexual and intimate partner violence and stalking/harassment) in the past 12 months and since the age of 15. Population‐weighted, age‐adjusted, logistic regression was used to estimate the odds of violence by disability status and gender. Results : People with disabilities were significantly more likely to experience all types of violence, both in the past 12 months and since the age of 15. Women with disabilities were more likely to experience sexual and partner violence and men were more likely to experience physical violence. Conclusions : These results underscore the need to understand risk factors for violence, raise awareness about violence and to target policies and services to reduce violence against people with disabilities in Australia.